Dispelling the Myth of Patents as Non-Rivalrous Property: Patents as Tools for Allocating Scarce Labor and Resources - Gruner, Richard S. (Science and Technology Law Review, 2012)
The view of patents as non-rivalrous property is fundamentally flawed in a key respect that has been largely overlooked in the legal literature. Past scholarship has focused on downstream rivalry regarding the use of patented ideas, while neglecting upstream rivalry regarding the inputs to those ideas in many modern research settings, i.e., the efforts of inventors and the substantial research resources that support them. By reexamining the impacts of patents on allocations of scarce resources, this Article helps to clarify two important roles of patents in modern, large-budget innovation: First, patent-influenced rewards help to attract scarce resources to innovation projects that would otherwise be devoted to alternative ends. Second, patent-influenced rewards provide prioritizing information to persons allocating scarce resources, establishing a basis to compare the relative value of commitments of resources among innovation projects. As innovation projects assume ever larger and more central functions in the United States economy, patents in the areas addressed by this Article will only increase in importance. The function of patents in influencing the allocation of resources to invention production has received remarkably little attention in law review analyses to date. This Article aims to rectify this imbalance and highlight the important functions that patents play in producing innovations valued by the public.